Deoxynivalenol induces cell senescence in RAW264.7 macrophages via HIF-1α-mediated activation of the p53/p21 pathway - Li, Jiefeng; Wang, Xu; Nepovimova, Eugenie; Wu, Qinghua; Kuca, Kamil (Toxicology, 2024)
Deoxynivalenol (DON), a potent mycotoxin, exhibits strong immunotoxicity and poses a significant threat to human and animal health. Cell senescence has been implicated in the immunomodulatory effects of DON; however, the potential of DON to induce cell senescence remains inadequately explored. Emerging evidence suggests that hypoxia-inducible factor-1α (HIF-1α) serves as a crucial target of mycotoxins and is closely involved in cell senescence. To investigate this potential, we employed the RAW264.7 macrophage model and treated the cells with varying concentrations of DON (2-8 μM) for 24 h. Transcriptome analysis revealed that 2365 genes were significantly upregulation while 2405 genes were significantly decreased after exposure to DON. KEGG pathway enrichment analysis demonstrated substantial enrichment in pathways associated with cellular senescence and hypoxia. Remarkably, we observed a rapid and sustained increase in HIF-1α expression following DON treatment. DON induced cell senescence through the activation of the p53/p21WAF1/CIP1 (p21) and p16INK4A (p16) pathways, while also upregulating the expression of nuclear factor-κB, leading to the secretion of senescence-associated secretory phenotype (SASP) factors, including IL-6, IL-8, and CCL2. Crucially, HIF-1α positively regulated the expression of p53, p21, and p16, as well as the secretion of SASP factors. Additionally, DON induced cell cycle arrest at the S phase, enhanced the activity of the senescence biomarker senescence-associated β-galactosidase, and disrupted cell morphology, characterized by mitochondrial damage. Our study elucidates that DON induces cell senescence in RAW264.7 macrophages by modulating the HIF-1α/p53/p21 pathway. These findings provide valuable insights for the accurate prevention of DON-induced immunotoxicity and associated diseases.
Keywords: RAW 264.7 Cells; Animals; Tumor Suppressor Protein p53; Cyclin-Dependent Kinase Inhibitor p21; makrofágy; stárnutí buněk; faktor 1 indukovatelný hypoxií - podjednotka alfa; Mice; Macrophages; signální transdukce; myši; Signal Transduction; Trichothecenes; inhibitor p21 cyklin-dependentní kinasy; RAW 264.7 buňky; nádorový supresorový protein p53; Hypoxia-Inducible Factor 1, alpha Subunit; trichotheceny; zvířata; Cellular Senescence